Factors Influencing Turnover Intention in a Malaysian Manufacturing Company - Ezaili Alias, N; Hazieqah Rohmanan, N; Ismail, S; Koe, W-L; Othman, R (KnE Social Sciences, 2018)
Turnover intention is defined as a process of employee to leave the current job or his willingness to separate from the organization. Truthfully, the talent of one employee cannot be inherited or be same by others new employee, thus, the need to retain the employee talents are crucial for employers and organizations to face the challenges in today’s intense global competition. Employee turnover has become most important issues to most organizations, hence, this issue still need a special attention since it can affect organizational performance. However, in retaining employees, organization cannot escape from exposing their workforce to higher level of work stress in order to achieve high demands and targets. Thus, the main objective of this paper is to examine the relationship between job stress, work engagement, job satisfaction and organizational commitment and employee turnover intention among manufacturing employees in Malaysia. A total of 170 employees were surveyed through a self-administered questionnaire. Statistical Package for Social Science (SPSS) version 20 was employed to perform data analysis of the study. Descriptive, Correlations and Regressions Analyses were performed and the findings revealed that there is significant relationship between work engagement, job satisfaction and organizational commitment and turnover intention. While no significant relationship was found between job stress and turnover intention. Keywords: turnover intention, job stress, work engagement, job satisfaction and organizational commitment.